The impact of different filter baskets, heights of perforated disc and amount of ground coffee on the extraction of organics acids and the main bioactive compounds in espresso coffee. (July 2020) - Khamitova, Gulzhan; Angeloni, Simone; Fioretti, Lauro; Ricciutelli, Massimo; Sagratini, Gianni; Torregiani, Elisabetta; Vittori, Sauro; Caprioli, Giovanni
Graphical abstract: Highlights: Optimization of espresso coffee extraction can foster sustainable coffee industry. The amount of ground coffee powder can be reduced by auxiliary devices. Filter baskets and perforated discs can help reduce the amount of ground coffee. A new HPLC-VWD method has been developed for organic acids and bioactive compounds. Chemical analyses were benchmarked with the results of sensory evaluation. Abstract: Espresso coffee (EC) is a complex and much appreciated beverage among coffee consumers. The extraction phase of EC, a combination of physical and chemical variables in a very short time, has a direct effect on the flavour of the beverage. This research aims to optimize the extraction process of EC by decreasing the amount of ground coffee from 14 g to 12 g (double cup), while keeping constant the particle size of ground coffee and the physical parameters of the espresso machine, making use of the following accessories: two different filter baskets, and four different heights of perforated discs (4–7 mm). Quantitative analyses on several organic acids (acetic, citric, caffeic, malic, tartaric) and caffeine, trigonelline, nicotinic and 5-caffeoylquinic acid are carried out with HPLC-VWD through a newly developed method. This combines the quantification of organic acids, obtained through HPLC-VWD, with the results of a sensory panel evaluation on the descriptive notes of EC. The outcomes will trigger and support further studies on different extraction processes, to develop more sustainable and economically affordable coffee of high quality.